Uniform Crime Reports (United States): Supplementary Homicide Reports, 1976-1983 - Fox, James Alan ([Verlag nicht ermittelbar], 1987)
These Uniform Crime Reports supplementary homicide data provide incident-level information on criminal homicides including information on the date, location, circumstances, and method of offences, as well as demographic characteristics of victims and perpetrators and the relationship between the two.